2021
DOI: 10.1093/jxb/erab514
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall modifications by α-XYLOSIDASE1 are required for control of seed and fruit size in Arabidopsis

Abstract: Cell wall modifications are of pivotal importance during plant development. Among cell wall components, xyloglucans are the major hemicellulose polysaccharide in primary cell walls of dicots and non graminaceous monocots. They can connect the cellulose microfibril surface to affect cell wall mechanical properties. Changes in xyloglucan structure are known to play an important role regulating cell growth. Therefore, the degradation of xyloglucan is an important modification that alters the cell wall. The α-XYLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 62 publications
(65 reference statements)
4
26
0
Order By: Relevance
“…Interestingly, while XyG-deficient A. thaliana xxt mutants exhibit only minor morphological phenotype changes, xyl1 mutants lacking α-xylosidase enzyme activity exhibit altered XyG side chains, free XyG oligosaccharide accumulation, and specific phenotypic defects during reproduction, seed dispersal, germination, and seedling growth. Di Marzo et al (2022) demonstrate that the expression of the XYL1 gene is directly regulated in developing seeds and fruits by the STK transcription factor.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Interestingly, while XyG-deficient A. thaliana xxt mutants exhibit only minor morphological phenotype changes, xyl1 mutants lacking α-xylosidase enzyme activity exhibit altered XyG side chains, free XyG oligosaccharide accumulation, and specific phenotypic defects during reproduction, seed dispersal, germination, and seedling growth. Di Marzo et al (2022) demonstrate that the expression of the XYL1 gene is directly regulated in developing seeds and fruits by the STK transcription factor.…”
mentioning
confidence: 81%
“…Xyloglucan (XyG), the predominant hemicellulose, is composed of a β-1,4-glucan backbone that is consecutively substituted with α-1,6-linked xylosyl residues ( Frankova et al , 2013 ; Pauly et al , 2016 ). Di Marzo et al (2022) demonstrated that the MADS-box transcription factor SEEDSTICK (STK) specifically controls seed and fruit biology by α-xylosidase (XYL) mediated XyG remodelling.…”
mentioning
confidence: 99%
See 3 more Smart Citations